Characteristics and influencing factors of 11C-CFT PET imaging in patients with early and late onset Parkinson’s disease - Kangli, Fan; Hongguang, Zhao; Yinghua, Li; Xiaoxiao, Du; Yuyin, Dai; Lulu, Gao; Yi, Li; Zhihui, Sun; Ying, Zhang (Frontiers in Neurology, 2023)
Objective This study aims to explore the difference between 11C-methyl-N-2β-carbomethoxy-3β-(4-fluorophenyl)-tropanel (11C-CFT) positron emission tomography (PET) imaging in the early-onset Parkinson’s disease (EOPD) and late-onset Parkinson’s disease (LOPD), and to analyze the correlation between 11C-CFT PET imaging and disease duration, Hoehn & Yahr (H&Y) stage, motor symptoms, and non-motor symptoms in patients with idiopathic Parkinson’s disease (PD), so as to explore its application value in assessing the severity of Parkinson’s disease. Materials and methods A total of 113 patients with idiopathic PD were included in this study. The patients were divided into EOPD and LOPD groups according to the age of 60 years, of which 58 were early-onset and 55 were late-onset. All patients underwent 11C-CFT PET imaging and manually sketched regions of interest (ROI) to delineate the caudate nucleus, anterior putamen, and posterior putamen ROI layer-by-layer, and the corresponding values were recorded. Clinical data [age of onset, disease duration, H&Y stage, total Unified Parkinson’s Disease Rating Scale (UPDRS) score, UPDRS III score, tremor score, postural instability/gait difficulty (PIGD) score, rigidity score, bradykinesia score, and Montreal Cognitive Assessment (MoCA) score] were collected from all patients. The differences in striatal 11C-CFT uptake between patients with EOPD and LOPD were compared, and the correlation between striatal 11C-CFT uptake and the clinical data of patients with idiopathic PD was evaluated. Results The caudate nucleus 11C-CFT uptake was higher in EOPD than in the LOPD group (t = 3.002, p = 0.003). 11C-CFT uptake in the caudate nucleus in patients with PD was negatively correlated with the age of onset, H&Y stage, disease duration, total UPDRS score, UPDRS III score, rigidity score, and bradykinesia score (p < 0.05). The anterior and posterior putamen 11C-CFT uptake was negatively correlated with H&Y stage, disease duration, total UPDRS score, UPDRS III score, PIGD score, rigidity score, and bradykinesia score (p < 0.05). Conclusion 11C-CFT PET provides an objective molecular imaging basis for the difference in disease progression rates between patients with EOPD and LOPD. Secondly, 11C-CFT PET can be used as an important objective indicator to assess disease severity and monitor disease progression.